Dysembryoplastic Neuroepithelial Tumor : A Case Report - Kintarak, Jutatip; Sangruchi, Tumtip (Siriraj Medical Journal, 2003)
We report on a classic case of dysembryoplastic neuroepithelial tumor (DNT) located in the right temporal lobe of a 12-years-old Thai boy presenting with visual, auditory and gustatory hallucinations for 4 years. DNT is an uncommon low-grade neuronal and mixed neuronal-glial tumor which has a characteristic clinical presentation, as well as characteristic radiological and histopathological finding. DNT has excellent prognosis and surgery is mainly curative treatment. Hence, it is important to recognize this entity in order to avoid unwarranted radio-or chemotherapy.